MORFOFISIOLOGI AKAR MELALUI INTERVAL PENYIRAMAN, PEMBERIAN MIKORIZA DAN MODIFIKASI MEDIA TANAM PADA PEMBIBITAN KAKAO (Theobroma cacao L.) - Kurniawan, Dedi (Jurnal Online Pertanian Tropik, 2017)
Cacao is an annual plant that plants in tropics and sensitive to the lack of water. This thing indicates the important role of media usage that can absorb and restrain in a large amount of water and also mycorrhizae role that can restrain the necessary of the plant water and increase the seedling's prosperity to stand in the water condition of the low ground. This objective of this experiment purposed to determine the watering interval, concentration of mycorrhizae, and the best growing media for cocoa seedlings. Experiments were carried out in the Kassa house Tobacco Deli and Cane Research Institute Medan, Province of North Sumatera, from July 2016 until October 2016. The design environment that was used in this study was Randomized Block Design with the factorial pattern. The first factor was the watering interval with three levels of watering interval: once of every 1, 3, and 5 days. The second factor was the inoculation of mycorrhizae consists of three levels: without inoculation of mycorrhizae, mycorrhizae inoculant 50 gr/plant and 100 gr/plant. The third factor was the growing media with four levels of growing media: soil, soil + fiber, soil + TKKS, and soil + sludge. Giving the watering interval once every 3 days and application of mycorrhizae with 100 gr/plant concentration on growing media of soil + fiber is the best treatment for the growth of cocoa seedlings.